Leituras intertextuais de O Tetraneto del-rei de Haroldo Maranhão - POMPEU, Thaís do Socorro Pereira (Universidade Federal do Pará, 2012)
This work focuses on researching Haroldo Maranhão‟s writing, trying to comprehend the aspects that influenced this autor, as well as the particularity of his writing, full of scholar features, in parallel with its obscene phrases and expressions of popular value. For accomplishing that, this work was based on an analysis of his great work Tetraneto Del-Rei, which presents issues related to our colonization period with a wealth of details, however under a different and reinterpretive prism from the various signs and elements manifested in the work of Haroldo. The image of the character Torto converges to the reinterpretive character, a Portuguese colonizer who stars moments of weakness, anxiety, fears and desires, feelings which are not included in previous works which have spread the imaginary of a hero in prose and verse. As a conceptual and literary allowance, we present precursors authors when compared to Haroldo Maranhão, seeking its relations with the style of those previous authors. Finally, this study aimed to demonstrate the presence of three intertextual elements in Tetraneto Del-Rei: new readings of the colonization process, the hat significance and the obscene possible interpretations.